THE ROLE OF ICT DEVELOPMENT IN PROMOTING ASEAN REGIONAL ECONOMIC CONVERGENCE - Ferry Prasetyia; Farah Wulandari Pangestuty; Dewanti Rahma Ariestiningtyas; Michael Hans (Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
Economic growth convergence is one of the economic targets that ASEAN countries aim to achieve through various initiatives and regional cooperation. To realize economic convergence, technology and information play a crucial role in accelerating economic growth in each country or region. As there has not been much research discussing the economic convergence in the context of technology and information among Southeast Asian countries, this study aims to uncover how technological innovation acts as a catalyst for economic growth convergence among ASEAN-5. The study uses secondary data from five ASEAN countries (ASEAN-5) from 2000 to 2020, sourced from the World Bank. The Generalized Method of Moments (GMM) is used to estimate the influence of technological and information developments on economic growth in ASEAN countries. The analysis results indicate that mobile phones have extensively penetrated ASEAN countries. This includes various social and economic groups, including communities in rural or remote areas without stable internet access. Mobile phones, especially basic phones (feature phones), remain the primary tool for communication and information access in many developing countries, including those in ASEAN.